Carbon capital: The lexicon and allegories of US hydrocarbon finance. Issue 2 (3rd April 2022) - Field, Sean
Abstract: Drawing on ethnographic fieldwork with energy financiers in Houston, Texas, this paper explores how experts use a lexicon of models and metrics to conceptualize and construct allegories about future hydrocarbon projects and companies. I show that allegorical narratives built with this lexicon advance a kind of energy ethics – distinguishing what is good and advocating for particular hydrocarbon futures. As the energy industry pivots toward renewables, I conclude that these metrics, models and allegories are coming to bear on new forms of extraction. This paper contributes to a better understanding of the financial and managerial processes on which extractive energy practices are imagined, valued and decided.